Association of ACTN3 and ACE gene polymorphisms with Indian elite boxer status - Grover, V. K.; Verma, J. P.; Kumar, A.; Sharma, N.; Tiwari, P. K. (Gene Reports, 2025)
Genetic variations are considered important for athletic performance. In this regard, a-actinin-3 (ACTN3) and angiotensin I-converting enzyme (ACE) gene polymorphisms are widely studied for their association with elite athlete status. The ACE gene regulates circulatory homeostasis, with the I variant of the ACE insertion/deletion (ACE I/D) gene polymorphism being associated with endurance performance, while the R allele of the R577X polymorphism of the ACTN3 gene, crucial for fast glycolytic muscle fibers, has been associated with speed and power performances. The present study investigated the association of these genetic variants with elite boxer (N = 57) status and compared with elite power/speed athletes (N = 40), endurance athletes (N = 44) and nonathletes (N = 98) in the Indian population. The R allele frequency was significantly higher in boxers than the nonathletes (p < 0.05). The allele and genotype frequencies of boxers, endurance and power/speed athletes did not differ significantly (p > 0.05). After analyzing the overall athletic cohort on the basis of their level of performance, the frequency of RR genotype (24.1 %) and R allele (47.7 %) in national level athletes was found significantly higher than in nonathletes (8.7 % and 34.2 %, respectively), with a significant difference (p < 0.05) between national level endurance athletes and nonathletes only. The ACE I/D gene polymorphism was not associated with any of the athletic cohorts (p > 0.05). Taken altogether, our study showed that the R allele of ACTN3 gene polymorphism is associated with elite boxer status as compared to the nonathletes.